(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: The objective of our study is to determine the frequency of non union in ipsilateral femur and tibia fractures treatment. Methods: This descriptive study included 30 patients having ipsilateral femur and tibia fractures in District Headquarter Hospital(DHQ)Teaching hospital Dera Ismail Khan( DI khan) from January 2016 to December 2018.Adult patients of either gender having ipsi lateral femur and tibia fractures fulfilling the inclusion criteria and treated surgically were included in this study. Postoperatively all the patients were seen at 2 weeks, and then every month till union is achieved. Results: In our study male were 27(90%) and female 3(10%).The mean age of our patients were 43±4SD. Femur interlocking nailing was done in 23(76.6%) cases and platting in 7(23.3%) cases, while tibia platting was done in 25(83.3%) cases and interlocking in only 5(16.6%) patients. A total of 11(36.6%) patients had non union. In 7(23.3%) patients femur alone went to non union while in 4(13.3%) patients femur non union was accompanied with tibia. Femur fractures treated with plating had a non union percentage of 20%(6 patients) while 5(16.6%) patients with interlocking nail reported non union.Among patients of tibial non union, 2(6.6%) had interlocking nail and 2(6.6%) had plating. All femur plates were replaced with interlocking nails and exchange nailing was done in all six interlocking femur nonunion cases. In all four tibial nonunion only bone grafting was added at nonunion site after refreshing the area. Conclusion: The frequency of non union in ipsilateral femur and tibia treatment is higher in femur than in tibia. Patients treated with femur platting had more chances of non union than with interlocking nail.